Magnetic Fe3O4/activated carbon for combined adsorption and Fenton oxidation of 4-chlorophenol. (15th October 2020) - Duan, Zhihui; Zhang, Wanhui; Lu, Muwen; Shao, Zhiwei; Huang, Weilin; Li, Jing; Li, Yanan; Mo, Juncheng; Li, Yongtao; Chen, Chengyu
Abstract: Development of composite adsorbents having high removal efficiency as well as convenient separation and regeneration properties is important for water treatment. This study synthesized magnetic activated carbon (MAC) from activated carbon (AC) by impregnation of iron oxides in the porous structure. Systematic characterization results demonstrated that MAC contained Fe3 O4 and had size of ∼0.5 mm, saturated magnetization of 8.99 emu/g, specific surface area of 473 m 2 /g, and pore volume of 0.54 cm 3 /g. Batch adsorption experiments were conducted using 4-chlorophenol (4-CP) as the probing pollutant and both MAC and AC as the adsorbents. Results showed that the adsorption rate followed intra-particle diffusion model and pseudo-second-order rate model, and that the adsorption equilibrium can fit to Freundlich isotherm equation. After adsorption, H2 O2 was added to initiate a heterogeneous Fenton reaction catalyzed by impregnated Fe3 O4 on MAC. More than 90% of aqueous 4-CP was degraded within 1 h, with optimal conditions of pH 3.0, 20 mM H2 O2, and Fe 2+ /Fe 3+ ratio of 3:1. After 5 cycles of adsorption-regeneration, the MAC composite remained >80% removal efficiency for 4-CP, indicating that it could be reused as an effective and retrievable adsorbent in water treatment of organic pollutants. Graphical abstract: Image 1 Highlights: MAC is synthesized by co-precipitation of Fe 2+ /Fe 3+ and used as an adsorbent for 4-CP. MAC impregnated with Fe3 O4 has magnetic feature, large SSA, and porous structure. 4-CP adsorption follows intra-particle diffusion model and Freundlich isotherm model. MAC can be regenerated via Fenton oxidation of 4-CP with addition of H2 O2. MAC may be used as a retrievable and regenerable adsorbent for water treatment.